Niektóre aspekty dydaktycznej analizy tekstu = Some aspects of didactic analysis of text - Kojs, Wojciech (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The author discusses the following questions: text as a didactic aid; connections of text with components of didactic process; analysis as a cognitive activity and the model of analysis - purposes, aids, methods, object and subject of analytical activity; controling and evaluating of analytical activity - the functions of control and valuation in the activity.
Keywords: tekst literacki; analiza